Treatment choices for the glycaemic management of patients with type 2 diabetes and chronic kidney disease: Analysis of the SAIL patient linked dataset. Issue 2 (April 2018) - Min, Thinzar; Davies, Gareth I.; Rice, Sam; Chess, James; Stephens, Jeffrey W.
Abstract: Aims: Chronic kidney disease (CKD) is common in type 2 diabetes and limits the treatment choices for glycaemic control. Our aim was to examine real-world prescribing for managing hyperglycaemia in the presence of CKD. Methods: The SAIL (Secure Anonymised Information Linkage) databank was used to examine prescribing during the period from the 1st of January to 30th December 2014. CKD was defined as:- none or mild CKD, eGFR ≥60 mL/min/1.73m 2 ; moderate CKD eGFR <60 mL/min/1.73m 2 ; and severe CKD eGFR <30 mL/min/1.73m 2 or requiring dialysis. Results: We identified 9585 subjects who received any form of glucose lowering therapy (8363 had no/mild CKD; 1137 moderate CKD; 85 severe CKD). There was a linear association between insulin use and CKD severity with approximately 54% of those with severe CKD receiving insulin. Sulphonylureas use did not differ among the CKD groups and was approximately 40%. Metformin showed a linear decrease across the groups, however approximately 21% in the severe CKD group received metformin. The use of dipeptidyl peptidase 4 inhibitors (DPP-4i) was approximately 20% and did not differ among groups. The DPP-4 inhibitor choice was:- 1% vildagliptin, 9% saxagliptin, 58% sitagliptin, and 32% linaglitpin. With respect to sitagliptin and saxagliptin, 72% and 62% received an inappropriately high dose in the setting of CKD. Conclusions: We observed that a considerable proportion of patients with type 2 diabetes and CKD were receiving metformin and non dose-adjusted DPP-4 inhibitors. Careful consideration of medication use and dosaging is required in the setting of CKD and type 2 diabetes.